The role of technology, organisation, and demand in growth and income distribution - Tommaso Ciarli; André Lorentz; Maria Savona; Marco Valente (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
The paper proposes a model that explains cross-country growth divergences over time for different aspects of structural change. The model formalises the links between production technology, firm organisation (functional composition of employment) on the supply side and the endogenous evolution of income distribution and consumption patterns on the demand side. Wage distribution is the main channel between the organisation of firms and consumption patterns, and firm selection is the main trigger of investment in new capital, productivity gains and cumulative growth. The model is able to reproduce empirical stylised facts on growth and income inequality associated with different stages of growth. We use VARs to estimate the causal relations between the three aspects of structural change. We then analyse the effect of the parameters that define the structure of an economy - and the way in which this unfolds through time - on growth and income distribution via numerical simulation. Product variety, differences in consumption preferences, organisational complexity and production technology determine whether the economy experiences a take-off or a stagnating growth, and the associated distribution of income.
Keywords: O41; L16; C63; O14; 330; structural change; growth; income distribution; consumption; technological change